Analysis of the productivity, impact, and collective hindex of the communication research carried out in Spain based on the information shared by researchers in their individual Google Scholar profiles. - Túñez López, M.; Martínez Solana, M. Y.; Valarezo González, K. P. (Revista Latina de Comunicación Social, 2014)
Introduction. This article examines the productivity, collective and individual h and h5 indexes, dissemination platforms (mainly books and journals), and visibility of the communication research carried out by Spanish scholars in the last four decades, based on the information shared by the 683 members of Spain's largest communication research association (AE-IC) in Google Scholar Metrics (GSM). Method. The study is based on the analysis of the information shared in GSM by 683 researchers, of which 142 have a public profiles and together have more than 7,000 publications. We analysed the dissemination platform, year of publication, number of citations, and title of the nearly 2,300 works that had received at least one citation. Results. The visibility of the area of communication is low. The average h-index is 4, while the global h-index for the community of communication researchers is 56, with an h5-index of 34: h-index of 44 and h5-index of 34 for articles, and h-index of 34 and h5-index of 13 for books. Four of every ten researchers had h-index of 0 while two of every three published works did not manage to receive a single citation. Individually, the highest h-index is 26 and the highest h5-index is 18. Meanwhile, the importance and impact of books and journals as dissemination platforms has been inverted. Before 1980, of each ten citations six were given to books and three to articles, but after 2010, of each ten citations three are given to books and seven to articles. In terms of differences across gender, female researchers have lower impact values than their male counterparts.